The Influence of Brand Image, Product Quality and Lifestyle Concerning Automobile Purchasing Decision of Mitsubishi Pajero Sport at PT. Sun Star Motor Semarang - Mayriza Rizki Laely; Handoyo D.W. (Jurnal Ilmu Administrasi Bisnis, 2018)
The development of the automotive world at this time feels so rapid that the competition is getting tighter. Companies are getting more and more engaged in various efforts to attract consumers to the products it produces. Specifically this study discusses the purchase of Mitsubishi Pajero Sport PT. Sun Star Motor Semarang during the year 2013-2015 continues to decrease in their sales. If it is not repaired and resolved, it will cause problems for PT. Sun Star Motor Semarang in the future.The purpose of this study is to determine the effect of brand image, product quality and lifestyle to the purchasing decision of Mitsubishi Pajero Sport. This type of research is explanatory research, using questionnaires a a data collection techniques. The population used in this research are consumers or car buyers of Mitsubihsi Pajero Sport PT. Sun Star Motor Semarang, with the number of samples taken is 90 respondents. This sample uses a purposive sampling technique, and uses a measuring scale by Likert. Analytical methods used are validity test, reliability test, classical assumption test, correlation test, determination test, simple linear regression, multiple linear regression, t test, and F test. This research is assisted by a computer program to process data which is SPSS.Based on the results of the research note that partially, brand image, product quality and lifestyle have a strong level of closeness relationship to the purchase decision. This is indicated by the results of multiple correlation coefficient test of 0.782. Significantly, the brand image, product quality and lifestyle variables are shown by the value of F count greater than F table that is 45,089> 3,952.Suggestions that can be given is to maintain a good image by always keeping in touch with consumers and customers. In addition, maintain and enhance the brand image and improve its shortcomings, add more to the interior and exterior facilities and apply more innovation to the products in order to adapt to competitor's products.